REFORMULASI PENGATURAN TINDAK PIDANA PENINDASAN (VERBAL BULLYING) YANG MENGAKIBATKAN KEMATIAN PADA ANAK - Dedek Putra; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Verbal bullying is this type of intimidation done verbally or with bad words with the aim of belittling, hurting, and also looking down on others. bullying verbal bullying is a form of "toxic stress", the long-term health effects of verbal bullying events even leading to death, especially those that recur on the victim. The impact of verbal bullying (oppression) is still not widely known, whether done with words, statements or certain nicknames turned out to have a more powerful effect compared to bullying that is done physically or with bodily violence. To ensnare perpetrators of verbal bullying have been regulated in the Child Protection Act No. 35 of 2014 in the world of education in Article 54. First, the regulation on the current conditions regarding criminal bullying which results in death of children in Indonesian criminal law has not been implemented What should have been regulated in Law No. 35 of 2014 concerning child protection, only regulates in Article 54 the world of education. Second, the idea of regulating criminal bullying for future cases, the need for legal reform or revision of the Child Protection Law on verbal bullying in general, so that the existing law can be updated so that it can keep up with the times and so no similar case will be repeated in the future.This research method is a normative law, focusing more on the principle of legal certainty and is carried out on legal norms which are benchmarks for behavior or inappropriate behavior. Not yet running a verbal bullying regulation. Rules only become rules that are not realized if there is no control or supervision from people who have obligations, bullying cases. Lack of legal clarity in every case that is happening right now and the weak implementation of various verbal bullying regulations The need for a criminal law policy to realize the laws and regulations in order to be in accordance with the situation at a certain time (ius constitutum) and the future (ius constituendum).The need for a clear law in accordance with the development of the times in order to be able to run a rule to protect children who are victims of oppression (verbal bullying) resulting in death in children. The need for legal certainty from the authorities and the government can run a rule so that the same case does not recur in the future. It is hoped that the revision of the Child Protection Act No. 35 of 2014 in order to regulate the general (verbal bullying) not only in the world of education.Keywords: Bullying, Verbal Bullying, Legal Regulations